Impact performance of explosively formed projectile (EFP) into concrete targets - Hu, F.; Wu, H.; Fang, Q.; Liu, J.C.; Liang, B.; Kong, X.Z. (International journal of impact engineering, 2017)
•A series of explosively formed projectile (EFP) penetration/perforation test on concrete targets are conducted.•Effects of liner material, concrete type and target configuration on the impact performance of EFP are experimentally studied.•Spalling/scabbing crater dimensions of concrete targets are better reproduced by the modified HJC model.•Effects of explosive type, liner configuration, etc., on the impact performance of EFP are further numerically discussed. This paper addresses the impact performance of explosively formed projectile (EFP) formed by shaped charge (SC) on the concrete targets. Firstly, a series of EFP penetration/perforation test on concrete targets are conducted. By assessing the dimensions of front spalling and rear scabbing craters as well as the penetration borehole, the influences of SC liner material, concrete type and target configuration (monolithic and spaced) on the target damage are experimentally discussed. Secondly, by utilizing the multi-material Arbitrary Lagrange-Euler (ALE) algorithm, Fluid-Structure Interaction (FSI) method and erosion algorithm implemented in the finite element (FE) code LS-DYNA, and describing the concrete targets with the original and modified HJC models, the formation and impact processes of EFP are well reproduced. Furthermore, based on the validated constitutive models and the corresponding parameters, the influences of explosive type, liner configuration and thickness, first concrete panel and air interlayer thicknesses of spaced target on the impact performance of EFP are further discussed. The derived conclusions could provide helpful references for the analysis and design of the concrete protective structures, and the evaluation of the ballistic performance of EFP.